Human capital and sociological factors as determinants of entrepreneurship - Ferreto Gutiérrez, Eugenia (2018)
Building on a systematic review of the existing literature, this study analyzes how different forms of human capital—i.e., formal education and self-confidence in entrepreneurial skills— impact the entrepreneurial entry decision. For the empirical application, we used the adult population survey generated by the Costa Rica Global Entrepreneurship Monitor (GEM) for 2014. The results reveal that the entrepreneurial examples (role model) have a positive influence on the entrepreneurial decision. In addition, the fear of failure reduces the probability of entrepreneurship, while self-confidence in their entrepreneurial skills (perceived ability) is positively associated with entrepreneurial entry.